The Renewable Water Filtration Innovation From Palm Oil Mill Effluent Waste - Sufina Azzahra; Martha Rianna; Nabila Agustin (International Journal of Oil Palm, 2024)
Indonesia is the largest palm oil producing country in the world. According to data from the North Sumatra BPS in 2021, Palm Oil production was 5,311,884 tons. Every palm oil factory disposes of its liquid waste which results in waste pollution becoming a very crucial issue to be addressed immediately because it has many negative impacts. POME is rich in minerals and carbon, but POME waste is currently not fully utilized optimally. The purpose of this research is to produce the latest innovation in water filtration to realize SDGs 2045 on clean water and sanitation and to study the effectiveness of magnetic which will be applied as clean water filtration by utilizing POME waste and natural sand containing ?-Fe2O3, alumina (Al2O3) and magnetic minerals with well water as samples in this study. The combination of POME waste and natural sand with chemical synthesis and calcination methods at a temperature of 500oC as activation of activated carbon and magnetic metals. The results of the synthesis of POME and natural iron sand obtained solids in the form of black powder. In the VSM test, the magnetization versus magnetic field data of Fe3O4/activated carbon POME obtained a magnetic saturation value of 10.13 emu/g. In the XRD test results of activated carbon materials, composites of activated carbon iron oxide and iron oxide and the synthesis results have diffraction patterns similar to the XRD database from JCPDS and in the COD and BOD tests, it proves a decrease in COD and BOD levels in well water before and after filtration with a large range, this indicates the success of the filtration process. In the AAS test as an identification of Fe metal in well water samples, Fe metal becomes <0.00206 (mg/L) starting from 0.01 (mg/L).